Language Acquisition and Language Development in Early Childhood: Theoretical Perspectives and Implications for Education - Desty Puspita Sari; Nurul Arifiyanti (Sustainable, 2025)
Language acquisition in early childhood is a fundamental developmental process that forms the foundation for children’s cognitive, social, emotional, and academic growth. This study aims to explore the process of language acquisition and language development in early childhood within natural learning environments. Employing a qualitative descriptive approach, data were collected through naturalistic observation, semi-structured interviews with teachers, and documentation in early childhood education settings. The findings indicate that children’s language development emerges through a dynamic interaction between innate linguistic capacity, cognitive maturation, behavioral reinforcement, and social–emotional engagement. Children acquire language most effectively through meaningful interaction, repeated exposure, and supportive communication in everyday activities. The results also reveal that social interaction and emotional security significantly enhance children’s motivation to communicate, while cognitive readiness influences the complexity of language structures produced by children. These findings suggest that early childhood language acquisition cannot be explained by a single theoretical perspective but should be understood as a multidimensional process. Therefore, early childhood education programs should adopt holistic and interaction-based approaches that integrate linguistic, cognitive, and socio-emotional stimulation to support optimal language development.